Does Perdeuteration Increase the Polarity of Janus Face Cycloalkanes?. Issue 2 (31st January 2023) - Fang, Zeguo; Yu, Cihang; Bühl, Michael; O'Hagan, David
Abstract: Stimulated by a suggestion of the late Professor Jack D. Dunitz, that perdeuterated Janus face cycloalkanes may be more polar than their unlabelled forms, the deuterated isotopologue of all cis‐1, 2, 3, 4, 5, 6‐hexafluorocyclohexane ([ 2 H6 ]‐1a ) and all cis‐1, 2, 3, 4‐tetrafluorocyclopentane ([ 2 H6 ]‐3a ) were prepared. Computation at the B3LYP−D3 level indicated that [ 2 H6 ]‐1a is not more polar than its protio form 1, however perdeuterated cyclopentane [ 2 H6 ]‐3a may indeed be more polar than 3, although the magnitude is predicted to be small. None‐the‐less retention time analysis on a reverse phase GC/MS column of an add‐mix of 3 and [ 2 H6 ]‐3a gave some indication that the per‐deuterated isotopologue 3a was detected marginally before the unlabelled compound consistent with increased polarity associated with perdeuteration. Abstract :